Endosymbiotic Evolution of Algae, Secondary Heterotrophy and Parasitism - Oborník, Miroslav (Biomolecules, 2019)
Photosynthesis is a biochemical process essential for life, serving as the ultimate source of chemical energy for phototrophic and heterotrophic life forms. Since the machinery of the photosynthetic electron transport chain is quite complex and is unlikely to have evolved multiple independent times, it is believed that this machinery has been transferred to diverse eukaryotic organisms by endosymbiotic events involving a eukaryotic host and a phototrophic endosymbiont. Thus, photoautotrophy, as a benefit, is transmitted through the evolution of plastids. However, many eukaryotes became secondarily heterotrophic, reverting to hetero-osmotrophy, phagotrophy, or parasitism. Here, I briefly review the constructive evolution of plastid endosymbioses and the consequential switch to reductive evolution involving losses of photosynthesis and plastids and the evolution of parasitism from a photosynthetic ancestor.
Keywords: symbióza; Heterotrophic Processes; Chlorophyta; Electron Transport; phagotrophy; Symbiosis; transport elektronů; parasitism; heterotrofní procesy; plastid; secondary heterotrophy; evolution; photosynthesis; endosymbiosis